Método de Karmarkar - Juan Félix Avila Herrera (Revista de Matemática: Teoría y Aplicaciones, 2012)
This is the first of a series of two articles in wich we study the Karmarkar’sAlgorithm.In this article we present a new approach that will be called the Karmarkar’s method. We intent to present a version of this algorithm that could be implemented easily.